Evaluation of Elastic Hardness of Bodies Using Pendulum Method - I. Z. Gilavdary (Наука и техника)
The content of «hardness» concept is considered in the paper. It has been shown that existing pendulum method used to measure elastic hardness is reduced to measuring of rolling friction. A new method is proposed to measure elastic hardness of bodies on the basis of previously ascertained effect of abnormal behavior of pendulum oscillation period with rolling-contact support in the region of small amplitudes. The mathematical model which explains this effect by elastic deformation of flat stationary pendulum support is offered in the paper. The value of curvature radius of support deformation is proposed to be considered as a quantitative characteristic of elastic hardness. The elastic hardness of sapphire, hard alloys, hardened steel, glass and brass are calculated.